2007
DOI: 10.1007/s10778-007-0052-4
|View full text |Cite
|
Sign up to set email alerts
|

Limiting state of an elastoplastic orthotropic plate with a periodic system of collinear cracks

Abstract: A modified Dugdale model is used to study the fracture of an orthotropic elastoplastic plate with a periodic system of rectilinear cracks. The material of the plate obeys a general yield criterion. The general form of solution is obtained in terms of Kolosov-Muskhelishvili potentials. The size of the plastic zone is expressed in terms of the external load and geometrical parameters. The equations for the determination of the stresses in the plastic zone and the crack opening displacement are derived. The effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…Numerous studies regarding this subject were done in the literature [18][19][20][21][22][23]. Analytic solutions for stress distribution and crack interaction for a composite material containing two collinear cracks can be found in the works [24][25][26][27][28][29]. The problem of three collinear crack interaction, elastic fields distribution and crack propagation using the integral equations method were studied in [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies regarding this subject were done in the literature [18][19][20][21][22][23]. Analytic solutions for stress distribution and crack interaction for a composite material containing two collinear cracks can be found in the works [24][25][26][27][28][29]. The problem of three collinear crack interaction, elastic fields distribution and crack propagation using the integral equations method were studied in [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…In the present paper, on the basis of the general solution obtained in [1,9] and the Hoffman strength criterion [2], we investigate the influence of the anisotropy of the material (the differences between moduli of elasticity along axes of orthotropy and between the ultimate tensile strength and ultimate compressive strength) on the limit state of a thin orthotropic plate weakened by a periodic system of collinear cracks under conditions of biaxial external loading.…”
Section: Introductionmentioning
confidence: 99%
“…An extensive review of relevant studies can be found in [3]. The limit state of an orthotropic plate with periodic cracks is analyzed in [12,13]. The stress-strain state of spherical shells with an eccentric circular hole and prestressed shells was studied in [14,18].…”
mentioning
confidence: 99%
“…( )are continuous functions, which can be expressed in terms of the regular parts of the kernels K ij 0 of (5) and the functions h i .In accordance with(12), the functions R x j ( )are represented as…”
mentioning
confidence: 99%